Eavesdropping on hell : historical guide to Western communications intelligence and the Holocaust, 1939-1945 - Hanyok, Robert J. (United States cryptologic history. World War II, 2005)
"A study of how Allied communications intelligence organizations reported intelligence on the Holocaust. Explains how the Western COMINT system operated during WWII; describes how the wartime records of SIS and GC & CS are organized in the U.S. and UK; summarizes what information is available from SIGINT records about the Holocaust"--Resource description page.